2006
DOI: 10.1080/j.1440-1614.2006.01802.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Quality of Life and Related Risk Factors for a Taiwanese Village Population 3 Years Post-Earthquake

Abstract: The QOL for earthquake survivors with psychiatric disorders, especially PTSD or MD, was inferior compared with the mentally healthy analogues, with contemporaneous decreases in mental and physical function scores across the QOL subscales. The persistence of long-term economic problems was one of many important factors affecting QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
3
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 21 publications
4
73
3
2
Order By: Relevance
“…Interestingly, we found also that sleep disturbance significantly influenced the physical aspect as well as the mental aspect of life quality in firefighters. The results were similar to that of disaster survivors [12,13]. As we know, insomnia is a criterion of PTSD as well as major depression, so sleep disturbance may be a confounder of PTSD and major depression.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Interestingly, we found also that sleep disturbance significantly influenced the physical aspect as well as the mental aspect of life quality in firefighters. The results were similar to that of disaster survivors [12,13]. As we know, insomnia is a criterion of PTSD as well as major depression, so sleep disturbance may be a confounder of PTSD and major depression.…”
Section: Discussionsupporting
confidence: 81%
“…Our previous studies [3,12,13] also reported that major life stresses contribute to depression, and depressive illness is often accompanied by marked reductions in quality of life. The PTSD patients had similar results [12][13][14]. Therefore, documenting psychosocial stressors and assessing the functional indices of illness that affect quality of life may be advantageous.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…rescuing people, and identification or recovery of or search for victims and human remains) [12] were not consistently associated with lower HRQoL. In previous studies post-traumatic stress disorder was found to influence the impact of disasters on HRQoL [33][34][35]. However, in the present study, adding post-traumatic stress symptoms to the regression models with regard to the physical and mental composite scores did not essentially change the difference between exposed and non-exposed workers, nor did it change the multivariate associations with types of exposure.…”
Section: Discussionmentioning
confidence: 84%
“…Similar results have been reported by other studies which evaluate the quality of life in populations affected by a disaster. For instance, a study [25] reported a poor quality of life in the victims of Chi-Chi earthquake 3 years later, and another [11] with a longitudinal design found that the victims of the earthquake had an impaired quality of life in the physical, psychological and environmental domains 3 months after the disaster, and in the psychological and environmental domains 9 months later. In other types of disasters, such as floods, or hurricanes [13,26,27] also a poorer QoL in the three domains (physical, psychological and environmental) in victims compared to controls was reported.…”
Section: Discussionmentioning
confidence: 99%